Targeted bile acid profiles reveal the liver injury amelioration of Da-Chai-Hu decoction against ANIT- and BDL-induced cholestasis - Zhou, YueHua; Zhou, YunZhong; Li, YiFei; Sun, Wei; Wang, ZhaoLong; Chen, Long; He, Ye; Niu, XiaoLong; Chen, Jialiang; Yao, Guangtao (Frontiers in Pharmacology, 2022)
Multiple types of liver diseases, particularly cholestatic liver diseases (CSLDs) and biliary diseases, can disturb bile acid (BA) secretion; however, BA accumulation is currently seen as an important incentive of various types of liver diseases’ progression. Da-Chai-Hu decoction (DCHD) has long been used for treating cholestatic liver diseases; however, the exact mechanisms remain unclear. Currently, our study indicates that the liver damage and cholestasis status of the α-naphthylisothiocyanate (ANIT)-induced intrahepatic cholestasis and bile duct ligation (BDL)-induced extrahepatic cholestasis, following DCHD treatment, were improved; the changes of BA metabolism post-DCHD treatment were investigated by targeted metabolomics profiling by UPLC-MS/MS. DCHD treatment severely downregulated serum biochemical levels and relieved inflammation and the corresponding pathological changes including necrosis, inflammatory infiltration, ductular proliferation, and periductal fibrosis in liver tissue. The experimental results suggested that DCHD treatment altered the size, composition, and distribution of the BAs pool, led the BAs pool of the serum and liver to sharply shrink, especially TCA and TMCA, and enhanced BA secretion into the gallbladder and the excretion of BAs by the urinary and fecal pathway; the levels of BAs synthesized by the alternative pathway were increased in the liver, and the conjugation of BAs and the pathway of BA synthesis were actually affected. In conclusion, DCHD ameliorated ANIT- and BDL-induced cholestatic liver injury by reversing the disorder of BAs profile.